Conservative critique, resisting regulation: Purposeful culture discourse in finance - Jack Kværnø-Jones; Anat Keller; Andreas Kokkinis; Crawford Spence (Finance and Society)
Culture is increasingly articulated by financial actors and financial firms as a solution to the dislocations of contemporary capitalism. It therefore matters, not just how actors behave, but how they articulate culture and what importance they accord it. Drawing on pragmatist sociology, the present paper takes this injunction seriously and reports the findings of a field study involving 29 interviews with senior members of financial firms whose understanding of culture and its importance were interrogated directly. The discourse concerning purposeful culture articulated in these interviews simultaneously recognises current arrangements between finance and society as fractured while positing organisational culture initiatives as the most realistic means of repairing said fracture. The paper draws on these findings to argue that, despite masquerading as a call for change, purposeful culture discourse has the effect of protecting against calls to rethink or radically transform the roles and effects of finance in society. The paper thus contributes to sociological perspectives on finance by illustrating how existing cultural discourse in financial markets serves as a kind of conservative critique where shortcomings are conceded in a way which insulates finance from wider structural change.